2010
DOI: 10.1016/j.brainres.2010.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Whisker stimulation increases expression of nerve growth factor- and interleukin-1β-immunoreactivity in the rat somatosensory cortex

Abstract: Activity-dependent changes in cortical protein expression may mediate long-term physiological processes such as sleep and neural connectivity. In this study we determined the number of nerve growth factor (NGF)-and interleukin-1β (IL1β)-immunoreactive (IR) cells in the somatosensory cortex (Sctx) in response to 2 h of mystacial whisker stimulation. Manual whisker stimulation for 2 h increased the number of NGF-IR cells within layers II-V in activated Sctx columns, identified by enhanced Fos-IR. IL1β-IR neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 67 publications
1
32
1
Order By: Relevance
“…There are several studies that demonstrated the expression of other IEGs or related proteins, such as c-Fos, in the S1BF. Manual whisker stimulation over the course of 8 days increased the number of growth factors within layers II–V in somatosensory cortex [32]. Also using immunohistochemistry, Filipkowski et al (2000) showed two novel approaches to induce whisker stimulation-initiated changes in gene expression of c-Fos in the S1BF: 1) manual whisker stimulation of one side of the rat’s myastacial pad for 20 minutes and 2) placing the rat in a novel wire cage in a dark sound-proof room for 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that demonstrated the expression of other IEGs or related proteins, such as c-Fos, in the S1BF. Manual whisker stimulation over the course of 8 days increased the number of growth factors within layers II–V in somatosensory cortex [32]. Also using immunohistochemistry, Filipkowski et al (2000) showed two novel approaches to induce whisker stimulation-initiated changes in gene expression of c-Fos in the S1BF: 1) manual whisker stimulation of one side of the rat’s myastacial pad for 20 minutes and 2) placing the rat in a novel wire cage in a dark sound-proof room for 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Waking neuronal activity drives the production of cytokines, establishing a link between local sleep intensity and prior waking activity. Expression of TNF-a and IL-1b is elevated in somatosensory cortex in response to whisker stimulation [56,57]. Both neurons and astrocytes are potential sources of cytokines in neocortex [26].…”
mentioning
confidence: 99%
“…IL1R is activated by IL1β, a known sleep regulatory molecule [1,5,6,7,8]. We show that this signaling mechanism must be intact in order for hypersomnolence to occur subsequent to METH-induced wakefulness.…”
Section: Discussionmentioning
confidence: 88%